Analisis Tingkat Literasi Masyarakat Kabupaten Kuningan Mengenai Zakat dengan Menggunakan Indeks Literasi Zakat (ILZ) - Dewi Tri Utami; Ikhwan Hamdani; Santi Lisnawati (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
This study aims to measure the Zakat Literacy Index (ILZ) of the Kuningan Regency community using the Simple Weighted Index method, which focuses on measuring a person's level of understanding and literacy on the object of zakat. Literacy and understanding of zakat is an external aspect that can determine a person in making decisions in paying zakat. The results of this study indicate that the Zakat Literacy Index (ILZ) of the Kuningan Regency community gets a value of 83.12 which is counted in the high literacy category. The highest indicator in this study is the variable knowledge of zakat in general with a score of 94.03. And the lowest indicator in this measurement lies in the variable knowledge of digital payment zakat with a score of 51.35. Keywords: Literacy, Measurement, Zakat Literacy Index